2022
DOI: 10.1111/bjh.18522
|View full text |Cite
|
Sign up to set email alerts
|

Early progression in follicular lymphoma in the absence of histological transformation or high‐risk Follicular Lymphoma International Prognostic Index still has a favourable outcome

Abstract: Although follicular lymphoma (FL) patients relapsing within 24 months after firstline treatment (POD24) have a poor prognosis, some cases show notable survival after first relapse (SF1R). We aimed to characterize the POD24 FL population and to identify the main prognostic factors at progression. We selected 162 POD24 patients (80F; median age at first relapse 59 years) from a cohort of 1067 grades 1-3a FL-treated patients. The remaining 905 patients treated with first-line immunochemotherapy and diagnosed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…For hematologic malignancies, the treatment effects and disease prognosis are mainly reflected by PFS and PPS. After reviewing the distribution of Follicular Lymphoma International Prognostic Index (FLIPI) scores of the patients in the clinical trials used as data sources in our model, we found that the patients who received R-mono and L-mono had a much lower proportion of high-risk FLIPI that could be correlated with poorer survival prognosis [ 15 ]. Thus, the health benefits associated with R-mono and L-mono could be overestimated in the cost–effectiveness analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For hematologic malignancies, the treatment effects and disease prognosis are mainly reflected by PFS and PPS. After reviewing the distribution of Follicular Lymphoma International Prognostic Index (FLIPI) scores of the patients in the clinical trials used as data sources in our model, we found that the patients who received R-mono and L-mono had a much lower proportion of high-risk FLIPI that could be correlated with poorer survival prognosis [ 15 ]. Thus, the health benefits associated with R-mono and L-mono could be overestimated in the cost–effectiveness analysis.…”
Section: Discussionmentioning
confidence: 99%